2020
DOI: 10.1039/d0gc02058c
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-driven catalysis: green ammonia synthesis with intermittent electricity

Abstract: Ammonia is one of the most produced chemicals, mainly synthesized from fossil fuels for fertilizer applications. Furthermore, ammonia may be one of the energy carriers of the future, when it...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
229
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(230 citation statements)
references
References 302 publications
(655 reference statements)
1
229
0
Order By: Relevance
“…Effectively, several studies carried out by using BaTiO 3 and glass as moderator materials revealed that the former performs better, even at temperatures above its Curie point. [49][50][51] As ferroelectric materials may act as catalysts for the ammonia synthesis and other plasma-catalysis processes, [49,50,52,53] the higher NH 3 yield obtained with PZT could also be due to a higher catalytic activity of this material as compared with that of BaTiO 3 . In addition, the highest BaTiO 3 current in Figure 4a for the same temperature range than for the experiment in Figure 5 supports the idea that electron impact processes directly related to the decomposition of the ammonia molecule [54] are more probable for BaTiO 3 than for PZT and might contribute to the observed relative decrease in efficiency of the former.…”
Section: Curie Transition Temperature and Packed-bed Reactor Efficimentioning
confidence: 99%
See 1 more Smart Citation
“…Effectively, several studies carried out by using BaTiO 3 and glass as moderator materials revealed that the former performs better, even at temperatures above its Curie point. [49][50][51] As ferroelectric materials may act as catalysts for the ammonia synthesis and other plasma-catalysis processes, [49,50,52,53] the higher NH 3 yield obtained with PZT could also be due to a higher catalytic activity of this material as compared with that of BaTiO 3 . In addition, the highest BaTiO 3 current in Figure 4a for the same temperature range than for the experiment in Figure 5 supports the idea that electron impact processes directly related to the decomposition of the ammonia molecule [54] are more probable for BaTiO 3 than for PZT and might contribute to the observed relative decrease in efficiency of the former.…”
Section: Curie Transition Temperature and Packed-bed Reactor Efficimentioning
confidence: 99%
“…Finally, we should mention that apart from the right moderator choice in terms of their dielectric properties, the incorporation of classical catalysts in packed-bed plasma reactors and the design of new ones are current challenges that will enable increasing the energy efficiency and yield of the processes to make them competitive regarding classical catalysis processes. [52,55]…”
Section: Curie Transition Temperature and Packed-bed Reactor Efficimentioning
confidence: 99%
“…[ 1b ] Therefore, it is very urgent to search a clean and sustainable process for the production of ammonia. Many methods have been proposed for the purpose, such as, electroreduction of nitrate to ammonia, [ 6 ] electrochemical nitrogen reduction reaction (e‐NRR), [ 7 ] photocatalytic NRR, [ 8 ] plasma‐chemical NRR, [ 9 ] biochemical photocatalytic NRR, [ 10 ] and chemical looping NRR. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia produced through ANF is utilized in multiple large-scale industries apart from fertilizers; examples include: pharmaceuticals, explosives, plastic manufacturing, mining and metallurgy, production of nitric acid, et cetera [8]. Recently there is an increasing interest in using ammonia as the energy carrier of the future [17,18]. Further increase in conventional ANF will be ecologically undesirable in terms of carbon footprint, therefore new environmentally-friendly methods for ANF are required [19].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the efficiency of ANF will lead to huge benefits on a world-wide scale. Multiple approaches ( Figure 1) have been undertaken to achieve this including: improvement of the H-B process conditions by exploring biological-mimics, homogeneous or heterogeneous catalysts designed to operate at milder conditions, semiconductor-based photocatalysis for nitrogen fixation, greener microwave plasma methods to synthesize ammonia and NOx, and hybrid systems between NNF and ANF such as development of synthetic rhizospheres (SRS), which helps intensify the NNF in plants via the development of a synthetic media [1,17,18,[20][21][22][23]. Binding of dinitrogen to a metal center depends on the formation of a stable reduced metal center, which can in turn reduce a dinitrogen molecule.…”
Section: Introductionmentioning
confidence: 99%